(untitled) (Medical Forum Monthly, 2024)
Introduction: Use of technology in modern education is inevitable. Nowadays the most common ways of lecture delivery include PowerPoint presentation, transparency overhead projector (TOHP) and black board (chalk and talk) methods. Limited researches are available to compare the effectiveness of these teaching tools in public sector universities of Pakistan. Our Objective was to compare the students’ perception regarding these three teaching tools in Dow Medical College Karachi. Study Design: A cross sectional, questionnaire based study. Place and Duration of Study: This study was conducted at Dow Medical College, Karachi from April to September 2010. Material & Methods: A cross sectional, questionnaire based, study was done. Questionnaire consists of MCQs, grading and open ended questions. A sample size of 314 subjects was taken including students from all current batches in Dow Medical College, Karachi. Information was collected to compare different features among Power Point presentation, transparency overhead projector (TOHP) and black board (chalk and talk) tools. Result: Our study depicted that student overall preferred the use of PowerPoint presentation in lectures than blackboard and overhead projector. The students have a more favorable response towards PowerPoint presentation than Blackboard and Transparency for better inclusion of content, understanding of text and figures, use of examples and illustrations and for summarizing the lecture. (p=<0.001). On the other hand, they preferred blackboard over Power Point presentations and transparency for facilitation of interaction between teacher and students, coping with teaching speed and stressing on important and relevant points. (p=<0.001). The result also indicated that the students considered blackboard and PowerPoint presentation equally effective than transparency to develop interest in learning and to grasp the contents. (p=<0.001) Conclusion: Our study concluded that PowerPoint presentation and Black Board teachings are equally important and should be used as an instruction tool for their respective aspects of learning. One teaching modality is not enough to cope up with student’s level of understanding and thus a combination of modern and traditional style of teaching should be incorporated.